alpha-lipoic acid protects against renal ischaemia-reperfusion injury in rats - YÜKSEL, MERAL; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (BLACKWELL PUBLISHING, 2008)
1. Oxygen free radicals are important components involved in the pathophysiological processes observed during ischaemia-reperfusion (I/R). The present study was designed to assess the possible protective effect of et-lipoic acid (ALA) on renal I/R injury. 2. Wistar albino rats were unilaterally nephrectomized and subjected to 45 min renal pedicle occlusion followed by 24 h reperfusion. Saline or ALA (100 mg/kg, i.p.) was administered 15 min prior to ischaemia and immediately before the reperfusion period. At the end of 24 h, rats were decapitated and trunk blood was collected. Creatinine, blood urea nitrogen (BUN) and lactate dehydrogenase (LDH) activity were measured in serum samples, whereas tumour necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, IL-6, 8-hydroxydeoxyguanosine (8-OHdG) and total anti-oxidant capacity (AOC) were assayed in plasma samples. 3. Kidney samples were taken for the determination of tissue malondialdehyde (MDA) and glutathione (GSH) levels, as well as Na/K-ATPase and myeloperoxidase (MPO) activity. The formation of reactive oxygen species in renal tissue samples was monitored using a chemiluminescence (CL) technique with luminol and lucigenin probes. Oxidant-induced tissue fibrosis was determined by tissue collagen content and the extent of tissue injury was analysed microscopically. 4. Ischaemia-reperfusion caused a significant increases in blood creatinine, BUN, LDH, IL-1 beta, IL-6, TNF-alpha and 8-OHdG, whereas AOC was decreased. In kidney samples from the I/R group, MDA, MPO, collagen and CL levels were found to be increased significantly; however, glutathione levels and Na/KATPase activity were decreased. Conversely, ALA treatment reversed all these biochemical indices, as well as histopathological alterations induced by I/R. 5. In conclusion, these data suggest that ALA reverses I/R-induced oxidant responses and improves microscopic damage and renal function. Thus, it seems likely that ALA protects kidney tissues by inhibiting neutrophil infiltration, balancing the oxidant-anti-oxidant status and regulating the generation of inflammatory mediators.
Keywords: cytokines; ischaemia-reperfusion; kidney; alpha-lipoic acid; myeloperoxidase; ISCHEMIA/REPERFUSION INJURY; SUPEROXIDE-DISMUTASE; OXIDATIVE STRESS; REACTIVE OXYGEN; FREE-RADICALS; AGED RATS; FAILURE; ANTIOXIDANT; MYELOPEROXIDASE; INFLAMMATION